Evaluation and comparison of portfolios formed by strategies through PE, PEG, PERG-SD, and PERG-Beta in the Tehran stock exchange - Hossein Eslami; Seyed Mohammad Moshashaei; Farzad Rahimzadeh (تصمیم گیری و تحقیق در عملیات)
Purpose: Making decisions to choose stocks and forming an accurate portfolio are always anxieties for investors. The primary purpose of this study is to evaluate and compare portfolios based on the fundamental strategies PE, PEG, PERG-SD, and PERG-Beta and find the best strategy for investing. Another goal of this research is to determine whether the strategies above can be superior to the TEDPIX index in the long term.Methodology: Our evidence includes 362 companies listed on the Tehran Stock Exchange from 2016 to 2023, and 110 have been selected as a research sample. The investment horizon in this study is three years (2021–2023), and investing is seasonal in the form of 12 seasons according to the mentioned strategies. The variable's value (strategy) is calculated for each strategy at the beginning of each season. All the companies are sorted from top to bottom based on the calculated variable (strategy) and divided into five equal categories. Then, for each portfolio category, investing was done at the beginning of the season. At the end of each season, the return and systematic risk of each category of portfolios were calculated. Finally, based on the risk and return of each portfolio, research hypotheses were tested using statistical tests (Wilcoxon and Friedman) and SPSS software.Findings: The results showed that the return of portfolios formed by low coefficients (LOW) is higher than the return of portfolios formed by high coefficients (HIGH) and the TEDPX index in all four strategies: PE, PEG, PERG-SD, and PERG-Beta. Also, based on Friedman's test, the low PE strategy has the best performance compared to other strategies.Originality/Value: This research fills a gap in the existing literature by organizing companies into five categories for each strategy, balancing portfolios seasonally, and analyzing the PERG strategy based on the nature of risk adjustment (systematic risk or total risk). These aspects have not been explored in previous internal research. Calculating the growth rate and systematic risk to evaluate these strategies differs from previous research. Moreover, no internal research has recently been conducted on these strategies, particularly during the research investment horizon (2021-2023). Given our country's ongoing political and economic changes (such as inflation, interest rates, the Corona pandemic, and the stock market crash in 2020), this research is crucial to confirm or challenge past findings in the highly dynamic investment environment.